Air bubble-induced intraocular lens opacification in hydrophobic intraocular lens following posttraumatic cataract surgery: A first-ever case report - G V Prabhakar (TNOA Journal of Ophthalmic Science and Research, 2017)
A 19 year old male presented with complaints of diminution of vision in right eye. He had undergone cataract surgery in right eye elsewhere 6 years ago for firecracker injury. On examination, eccentric pupil is noticed with intraocular lens (IOL) opacity. on dilatation, rest of the intraocular lens is clear. As the rest of the IOL, which was protected by iris, was noted to be clear, the opacification at pupillary area suggests it to be secondary to air bubble contact .IOL exchange was done and explanted was tested and got confirmed as hydrophobic material. There are cases reports of IOL opacification post intra cameral air injection in hydrophilic lenses, to our knowledge this is the first case report of IOL opacification in hydrophobic lenses. with this case report we want to highlight the fact that one should be careful before intracameral air injection in eyes with both types of IOL.